KESEHATAN DAN KESELAMTAN KERJA TERHADAP KINERJA PEGAWAI PADA BALAI BESAR INDUSTRI HASIL PERKEBUNAN MAKASSAR - Nurdin, Hikmah; Rahmatullah, Selfi (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
AbstractThe Makassar Plantation Products Industry Center (BBIHP) has established work safety programs for research employees, such as providing work safety tools for research employees including safety shoes, helmets, masks, glasses and gloves. But there is only one thing that causes work accidents that occur in the workplace, resulting in disruptions and decrease the spirit of employee performance. The population of this study is employees of the Makassar Plantation Products Industry Center which amounts to 122 employees with 83 civil servants and 39 non-civil servants. Samples in this study were taken based on parts per division, namely certain functional parts of the Center for Plantation Products Industry as many as 45 employees. The analysis used to find out if there is a positive and significant influence of independent variables (x_(1)and x_2) on dependent variables (Y) is multiple regression. Based on spss output statistical 22.0 for windows, the multiple linear regression equation can be formulated as follows: Y= 7,647 + 0.419 X_1+ 0.365 X_(2 ). The effect of occupational health and safety variables simultaneously positively affects employee performance is 30,698 with a significance value of 0.000. The effect of work health variables positively affect employee performance is 3,448 with a significant value of 0.001. The effect of work safety variables has a positive effect on employee performance is 3,046 with a significant value of 0.004. Keywords: Health and Work Slowness, Employee Performance.